DETERMINATION OF AMERICAN TYPE STOCK OPTION PRICE WITH DISTRIBUTION DEVIDEN USING FINITE ELEMENT METHOD - Nikenasih Binatari; Rosita Kusumawati; Ade Latif (Jurnal Penelitian Saintek, 2013)
Changes in stock price, either when the stock price increases or decreases, can be exploited for profit. One of the investment instruments that can be used to take advantage of the stock price change is a stock option. In addition, stock options can also be used to minimize the amount of losses that may be suffered by investors. One of the keys to take advantage of the stock options is the precision determination of the type of stock option exercise price. Black-Scholes model is a model that has been widely used as an approach to solve the problem of determining the exercise  transaction costs, risk-free interest rates, and changes in stock prices follow a random pattern. Meanwhile, most of the stock options are traded in fact pay dividends. Because the most heavily traded stock options is stock options American type, then the purpose of this study was to determine the Black-Scholes option pricing American type stock with the dividend model using finite element method. At case one year expiration date, execution price $10, risk-free interest rate 10%, paid dividend proportion 5%, stock price volatility 0,32, call option price at market $1,5 and put option price at market $6 then the result shows that call option price is $1,8 and put option price is $5,3. Because call option price is cheaper then investor better buy the option while for put option price, because it’s more expensive then investor better not buy the option.  price of stock options. The assumption of this model is not giving the stock dividend, no transaction costs, risk-free interest rates, and changes in stock prices follow a random pattern. Meanwhile, most of the stock options are traded in fact pay dividends. Because the most heavily traded stock options is stock options American type, then the purpose of this study was to determine the Black-Scholes option pricing American type stock with the dividend model using finite element method. At case one year expiration date, execution price $10, risk-free interest rate 10%, paid dividend proportion 5%, stock price volatility 0,32, call option price at market $1,5 and put option price at market $6 then the result shows that call option price is $1,8 and put option price is $5,3. Because call option price is cheaper then investor better buy the option